Inter-device reliability of wearable technology for quantifying jump height in collegiate athletes - Nickerson, B. S.; Medrano, N. F.; Perez, G. L.; Narvaez, S. V.; Carrillo, J.; Duque, M. (Biology of Sport, 2020)
The purpose of this study was to evaluate the inter-device reliability of three VERT devices (Mayfonk Athletic, Florida, USA) when worn on the waist (W), left-hip (LH), and right-hip (RH) during single- and double-leg counter movement jumps (CMJ) in collegiate athletes. Thirty-two female and twenty-eight male NCAA Division II athletes (n = 60) participated in the present study. Jump height (JH) values for double-leg CMJs were analyzed by each device using a one-way repeated measures ANOVA whereas a 2 (jump leg) x 3 (wear location) repeated measures ANOVA was employed to evaluate single-leg CMJs. Reliability of the VERT devices were based upon intraclass correlation coefficients (ICC). Double-leg CMJs revealed an excellent ICC between all three VERT devices (ICC = 0.969). However, JH for RH and LH (45.69 ± 9.84 and 45.82 ± 10.45 cm, respectively) were on average lower than W (50.44 ± 12.37cm; both p < 0.001). The ICCs were excellent for right- and left-leg CMJs (ICC = 0.939 and 0.941, respectively). However, an interaction was observed (p < 0.001). No differences existed for left- or right-leg when VERT was worn on the waist. However, JH was higher when VERT devices were worn on the opposite hip of the jump leg (i.e., LH>RH for right-leg CMJs; RH>LH for left-leg CMJs; all p < 0.001). Results suggest that LH and RH are interchangeable for double-leg CMJs, but not with waist despite excellent reliability. In addition, all wear locations provided excellent ICCs for single-leg CMJs. However, waist provides more consistent JH values for right- and left-leg CMJs while RH and LH show more variability.